Neoadjuvant chemotherapy with docetaxel, nedaplatin, and fluorouracil for resectable esophageal cancer: A phase II study. Issue 11 (25th September 2018) - Ohnuma, Hiroyuki; Sato, Yasushi; Hayasaka, Naotaka; Matsuno, Teppei; Fujita, Chisa; Sato, Masanori; Osuga, Takahiro; Hirakawa, Masahiro; Miyanishi, Koji; Sagawa, Tamotsu; Fujikawa, Koshi; Ohi, Motoh; et al.
Abstract : Cisplatin plus 5‐fluorouracil is regarded as standard neoadjuvant chemotherapy for esophageal squamous cell carcinoma (ESCC) in Japan, but the prognosis remains poor. We have previously described how definitive chemoradiotherapy with docetaxel, nedaplatin, and 5‐fluorouracil (DNF) led to a very high response rate and promising survival times. We therefore undertook a phase II trial to evaluate the feasibility and efficacy of neoadjuvant DNF. The study included patients with clinical stage Ib‐III ESCC. Chemotherapy consisted of i.v. docetaxel (30 mg/m 2 ) and nedaplatin (50 mg/m 2 ) on days 1 and 8, and a continuous infusion of 5‐fluorouracil (400 mg/m 2 /day) on days 1‐5 and 8‐12, every 3 weeks. After three courses of chemotherapy, esophagectomy was carried out. The primary end‐point was the completion rate of the protocol treatment. Twenty‐eight patients were enrolled (cStage Ib/II/III, 2/3/23) and all received at least two cycles of chemotherapy. Twenty‐five patients underwent surgery, all of whom achieved an R0 resection, leading to a completion rate of 89.3%. The overall response rate was 87.0%. A pathological complete response was confirmed in eight (32.0%) cases. Grade 3/4 adverse events included leukopenia (32.1%), neutropenia (39.3%), febrile neutropenia (10.7%), thrombocytopenia (10.7%), and diarrhea (14.3%), but were manageable. Treatment‐related deaths and major surgical complications did not occur. Estimated 2‐year progression‐free and overall survival rates were 70.4% and 77.2%, respectively. Thus, DNF therapy was well tolerated and deemed feasible, with a strong tumor response in a neoadjuvant setting for ESCC. This trial is registered with the University Hospital Medical Information Network (UMIN ID: 000014305). Abstract : This phase II study investigated a regimen of neoadjuvant chemotherapy for resectable esophageal squamous cell carcinoma using docetaxel, nedaplatin, and 5‐fluorouracil (DNF), which indicated that DNF was well tolerated and effective. A completion rate for protocol treatment was 89.3%, and all patients who underwent surgery achieved an R0 resection. The overall response rate was 87.0%, with a pathological complete response rate of 32.0%. The 2‐year survival rate was 77.2%.